Indoor air quality in schools and its relationship with children's respiratory symptoms - Madureira, J (2015)
A cross-sectional survey was conducted to characterize the indoor air quality (IAQ) in schools and its relationship with children's respiratory symptoms. Concentrations of volatile organic compounds (VOC), aldehydes, PM2.5, PM10, carbon dioxide, bacteria and fungi were assessed in 73 classrooms from 20 public primary schools located in Porto, Portugal. Children who attended the selected classrooms (n = 1134) were evaluated by a standardised health questionnaire completed by the legal guardians; spirometry and exhaled nitric oxide tests. The results indicated that no classrooms presented individual VOC pollutant concentrations higher than the WHO IAQ guidelines or by INDEX recommendations; while PM2.5, PM10 and bacteria levels exceeded the WHO air quality guidelines or national limit values. High levels of total VOC, acetaldehyde, PM2.5 and PM10 were associated with higher odds of wheezing in children. Thus, indoor air pollutants, some even at low exposure levels, were related with the development of respiratory symptoms. The results pointed out that it is crucial to take into account the unique characteristics of the public primary schools, to develop appropriate control strategies in order to reduce the exposure to indoor air pollutants and, therefore, to minimize the adverse health effects.